If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 34 = 1 Reorder the terms: 34 + 11x = 1 Solving 34 + 11x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + 11x = 1 + -34 Combine like terms: 34 + -34 = 0 0 + 11x = 1 + -34 11x = 1 + -34 Combine like terms: 1 + -34 = -33 11x = -33 Divide each side by '11'. x = -3 Simplifying x = -3
| 2m^7-7m^4+8m^9-6m^6= | | 8-x/5=-3 | | M+7+3=29 | | x/6+2=-3 | | x+3/2=8 | | t+40/7=20 | | w/2-60=45 | | 6mn-m^2+3n+5n^2-3mn= | | u-17/3=11 | | -0.5*32x^2+32x+12=0 | | X-6=-28 | | 4+7m-30-m+n= | | r+5/4=12 | | i/4-9=13 | | c/5+8+10 | | 22m^2-3mn+5mn-7+4m^2= | | 5x+2=9x+14 | | 1/3(2x-3)-1/2x=3/2x-2 | | 8n=111+5n | | 9x^6-21x^4/3x^3 | | 1/3(2x-3)-1/2x=3/2-2 | | 7m=128+3m | | 2g=14+g | | 9e+15=114 | | 7p-13=78 | | 2t-19=37 | | 27y/3 | | 3/4x-4=-7/8x+1 | | 8n-14=-38+5n | | 5m-16=-40+9m | | 8x-[-11x+[11x-(-6x+19)]]=0 | | -0.5*32x^2+12x+22=23.76 |